Une théorie réaliste des prix et de la production - Beach, E. (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractThe assumption of a single price at any time is very generally imposed on market theorizing. It is unrealistic, but generally accepted because of the needs of welfare theory, and of current theoretical methods. In order to evaluate the significance of the loss in realism from the use of this assumption, it seems to be worthwhile to start with the other extreme of complete ignorance in a market, and allow buyers and sellers to pair off at random, allowing a diversity of prices. It is very interesting that in such a "blind market" the quantity traded tends to be larger, by about 44 per cent.The theory of such a market can be based on a Marshallian industry, and many different versions are suggested. The theory does seem to give useful insight into the results of imposing uniform pricing by barbers, and uniform wage rates in labour markets. The loss in trade and employment seems to be great enough that we should examine a little more carefully the arguments that have been accepted so easily that such uniformity implies greater equity.